Pendidikan, Seni, dan Budaya: Entitas Lokal dalam Peradaban Manusia Masa Kini - Fajry Subhaan Syah Sinaga; Emah Winangsit; Agung Dwi Putra (Universitas Negeri Surabaya, 2021)
Humanizing and civilizing society is one manifestation of education as a cultural process. The educational process allows for the exchange of information between subjective, intersubjective, and intrasubjective and inherits the nature of values, knowledge, and beliefs that function as a guide to meet human needs in the context of local entities. This article is a conceptual research that discusses the educational process that can occur through several concepts, namely internalization, socialization, and enculturation. In the process, education can be done in formal, informal, or non-formal ways. This article aims to reveal the importance of the values ​​contained in local entities and preserve them as a form of cultural manifestation based on knowledge, values, beliefs that can benefit the community. In a more specific context, this article brings up the discourse of art education as a civilizing process that utilizes art as a medium that has a strategic role in preserving and strengthening the local entity of a culture.